Kapitalisme Digital dan Pendidikan Agama Islam:: Telaah Kritis terhadap Transformasi Nilai dan Media Pembelajaran dalam Era Disrupsi Digital - Muhammad Ridha; M. Andre Irawan (Tasqif: Journal of Islamic Pedagogy, 2025)
The development of digital technology has created great opportunities and challenges in the world of Islamic religious education. This article aims to critically examine how digital capitalism affects the dissemination of religious content and transformation in the Islamic education system, especially in relation to scientific authority, learning methods and curriculum. This research uses a qualitative approach with a literature study method, which relies on the analysis of books, journals, online articles, and digital da'wah content. The results show that digital capitalism has shifted religious authority from traditional scholars and teachers to digital public figures, whose credibility is determined more by media popularity than scientific competence. In addition, viral religious content tends to be superficial in substance but visually appealing, causing fragmentation of religious understanding among the younger generation. In facing this challenge, Islamic education needs to restructure its pedagogical approach by strengthening digital literacy, adapting the curriculum, and redefining the role of teachers as spiritual companions and facilitators of critical thinking. This study recommends the importance of technology integration in Islamic religious education that is ethical, reflective, and based on valid scientific values.